Innovación pedagógica y su incidencia en los resultados de aprendizajes en los estudiantes de la Escuela Dr. Francisco Martínez Aguirre, Vinces. 2022 - Cedeño Montece, Dayana Yusmeri (2023)
The purpose of this research project is to determine the way in which pedagogical innovation affects the learning results of the students of the Dr. Francisco Martínez Aguirre School, in the city of Vinces in 2022. Study with traditional learning methods in where the fundamental learning tool was memorization and the exams were the only proof of the student's performance. Currently there are other ways to do it. In short, today there are educational techniques that are designed to stimulate student learning, which focus on seeking participation and stimulation in learning. Learning focused on interaction with the environment and its conflicts, to develop various skills by actively contributing to them, providing solutions, guiding their actions, as well as learning to be active and responsible. Indicators of achievement can help track the progress of strategies and programs in education sector plans, optimizing the quality of education, comparing individual results over time, place or context, or against performance standards. overall reference. For the collection of information, the qualitative and quantitative methodology, descriptive, explanatory, exploratory and field research were improved; The interview and survey technique will need a strong basis for the research, the survey was applied to the students of the 5th year of EGB parallel "B", while the interview was directed to three teachers in the 2022-2023 school period.